Open Window Mapping of Accessory Pathways: A Literature Review and Practical Guide - Rajdip Dulai; Fatima Bangash; Ajay Sharma; Alex Cambridge; Geoff Wong; Wei Lim; David Farwell; Jason Garcia; Neil T Srinivansan (Arrhythmia & Electrophysiology Review)
Catheter ablation is the treatment of choice for patients with symptomatic accessory pathways (APs) causing recurrent atrioventricular reciprocating tachycardia or in situations where APs conduct rapidly, posing a risk of sudden cardiac death. Conventional AP mapping relies on point-by-point assessment of local electrograms looking closely for pathway electrograms or early atrial or ventricular electrograms, which may be challenging and time consuming. Recently, open window mapping (OWM) using 3D navigational systems has emerged as a novel technique to help localise and ablate APs. OWM has significant advantages over conventional point-by-point mapping techniques. The purpose of this review is to summarise the currently available literature on the OWM technique and to highlight the technical aspects and mapping considerations for OWM, including specific cases demonstrating its utility.